An injectable and photocurable methacrylate-silk fibroin hydrogel loaded with bFGF for spinal cord regeneration. (May 2022) - Zhou, Linquan; Wang, Zhenyu; Chen, Dehui; Lin, Jiemin; Li, Wenwen; Guo, Shengyu; Wu, Rongcan; Zhao, Xin; Lin, Taotao; Chen, Gang; Liu, Wenge
Graphical abstract: Highlights: Synthesized methacrylate-silk fibroin hydrogel with photocurable properties and is well suited for releasing bFGF. This hydrogel has good tissue compatibility and exerts certain anti-inflammatory effects on spinal cord injury. This hydrogel is first loaded with bFGF and shown to be beneficial to the repair of spinal cord injury. Abstract: The treatment of spinal cord injury is still a major clinical challenge today. Basic fibroblast growth factor (bFGF) is a biological factor that effectively promotes the recovery of nerve function after spinal cord injury. The focus of this study was to accurately and efficiently maximize the biological effects of bFGF locally. Therefore, we innovatively synthesized methacrylate-silk fibroin (SilMA) hydrogels for bFGF delivery. This hydrogel has photocurable properties and form a gel upon UV in 15 s. The hydrogel shows no obvious cytotoxicity in vitro and in vivo. Our results showed that SilMA@bFGF can releases bFGF slowly to promote the regeneration of nerve axons, inhibit glial cell proliferation and improve neuronal mitochondrial function. In the early stage of spinal cord injury in rats, the SilMA hydrogel also inhibit the local inflammatory reaction and oxidative stress compared with injury alone, which is more conducive to the repair of nerve function. This study is the first to apply a photocurable silk fibroin hydrogel to spinal cord injury and the result is satisfactory. This method will provide a new treatment strategy for spinal cord injury.